Japan and Asia Pacific integration : Pacific romances 1968-1996 - Korhonen, Pekka, 1955- (Sheffield Centre for Japanese Studies/Routledge series., 1998)
Japan and Asia Pacific Integration is a study of regional integration in the greater Pacific area during 1968-1996. It examines the political rationale of such international organisations as the Asia Pacific Economic Co-operation (APEC) forum, and the East Asian Economic Caucus (EAEC). There is a focus on Japanese conceptions of regionalism and integration, but the attitudes of other countries such as the United States, Australia, Malaysia and China are also explored.